Recurrent Dermatofibrosarcoma Protuberance and its Management with Radical Excision and Interval Skin Grafting: A Case Report - Ahmad, Imran (Iranian Society for Plastic Surgeons, 2016)

(untitled) (World J Plast Surg)
Dermatofibrosarcoma protuberans (DFSP) is very rare tumor of dermis layer of skin with the incidence of only 1 case per million per year. DFSP rarely leads to a metastasis (Less than 5% have metastasis), but DFSP can recur locally. We publish a rare case of a recurrent dermatofibrosarcoma protuberans and its management with radical excision and interval skin grafting.